2022
DOI: 10.3389/fped.2022.916655
|View full text |Cite
|
Sign up to set email alerts
|

Severe Outcomes Associated With SARS-CoV-2 Infection in Children: A Systematic Review and Meta-Analysis

Abstract: ObjectiveTo estimate the proportion of SARS-CoV-2 infected children experiencing hospitalization, intensive care unit (ICU) admission, severe outcomes, and death.Data SourcesPubMed, Embase, and MedRxiv were searched for studies published between December 1, 2019 and May 28, 2021. References of relevant systematic reviews were also screened.Study SelectionWe included cohort or cross-sectional studies reporting on at least one outcome measure (i.e., hospitalization, ICU admission, severe outcomes, death) for ≥10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…1,4 In a meta-analysis of 31 studies in hospitalized children, a cumulative mortality rate of 1.1% was reported. 5 The relatively higher rate of mortality in our study is partly due to the younger population; but other contributing factors, for which our dataset may not account for, need further and thorough investigation.…”
mentioning
confidence: 73%
“…1,4 In a meta-analysis of 31 studies in hospitalized children, a cumulative mortality rate of 1.1% was reported. 5 The relatively higher rate of mortality in our study is partly due to the younger population; but other contributing factors, for which our dataset may not account for, need further and thorough investigation.…”
mentioning
confidence: 73%
“…A striking finding in our cohort was that children <5 years old were relatively protected from SARS-CoV-2 infection, even with the more transmissible Omicron BA.1 variant. Many studies have reported that young children are protected from severe COVID-19 and are more likely to experience mild or asymptomatic infection 26 29 . Our data suggest that young children may be relatively protected from SARS-CoV-2 infection and not just severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Children infected with SARS-CoV-2 generally have mild symptoms, with reported mortality rates of <0.1% [ 6 , 22 - 25 ]. A significant number of children (15%–42%) are asymptomatic, whereas 18%–57% require hospitalization [ 25 - 29 ].…”
Section: Cardiovascular Involvement Of Sars-cov-2 In Childrenmentioning
confidence: 99%
“…In a European multicenter study of 582 individuals <18 years of age with polymerase chain reaction (PCR)-confirmed COVID-19, 8% of study participants required ICU admission, 4% required mechanical ventilation, 3% required inotropic support, and 1% required extracorporeal membrane oxygenation (ECMO) support [ 26 ]. A meta-analysis by Sumner et al [ 6 ] demonstrated that, among 973 hospitalized school-aged patients, 10.1% required ICU admission, 4.2% had a severe outcome, and 1.1% (95% confidence interval, 0.2%–2.3%) died.…”
Section: Cardiovascular Involvement Of Sars-cov-2 In Childrenmentioning
confidence: 99%
See 1 more Smart Citation